Podstawy działania izb gospodarczych w Polsce i w wybranych państwach Unii Europejskiej - Kmieciak, Robert (The basis of action of chambers of commerce in Poland and in chosen countries of the European Union, 2005)
The Polish membership in the European Union should contribute to the acceleration of the activities aiming at the forming of the representation of circles of entrepreneurs. The chambers of commerce should be credited with this. Defining the legal structure of the chambers one can refer to either the Anglo-Saxon experience or to the French (continental) solutions. Taking into account the past achievements of the Polish chambers of commerce and the effects of activities of the chambers placed in the system of public law one comes to the conclusion that it is the French model that should be particularly inspiring for the Polish legislature to define the organizational foundations of the economic self-government in our country. Undoubtedly, it guarantees not only the better representation of interests of business circles but also their stronger position in the political system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1090, s. 141-157